2016
DOI: 10.1002/bbb.1658
|View full text |Cite
|
Sign up to set email alerts
|

Use of linear programming to ‐optimize the social, −environmental, and economic impacts of using woody feedstocks for pellet and ‐torrefied pellet production

Abstract: Linear programming was used to optimize the economic, environmental, and social impacts of forest biomass used for bioenergy production. Sixteen scenarios (combinations of feedstocks, products, markets, and end use) were studied. Two feedstocks (roundwood and wood residues), two densifi ed bioenergy products (white pellet, torrefi ed pellet), two markets (domestic, international), and two end uses (power generation, district heating) were evaluated. The social, environmental, and economic sustainability attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In deterministic models, all parameters are given and deterministic. The optimal design and operation of bioenergy supply chains are formulated deterministically as linear programming [13,14], mixed integer linear programming [15,16], and mixed integer non-linear programming [17]. Deterministic models have been widely used for decades but have limitations because they are too idealistic in that all parameters or constraints have to be known and deterministic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In deterministic models, all parameters are given and deterministic. The optimal design and operation of bioenergy supply chains are formulated deterministically as linear programming [13,14], mixed integer linear programming [15,16], and mixed integer non-linear programming [17]. Deterministic models have been widely used for decades but have limitations because they are too idealistic in that all parameters or constraints have to be known and deterministic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although all of these processes have several unit operations in common, there are also some noteworthy differences between different designs. (Radics et al 2016) All torrefaction processes require some common unit of operations: a drier, some additional screening and size reduction, a torrefaction system, a system for combustion of torrefaction gases (and potentially biomass dust and drier vent gases), a cooling system, and a system for additional grinding and consolidation of the torrefied product. In addition, almost all of the systems move the biomass through the hot zone in a counter current with cold biomass being introduced in the lowest temperature zone.…”
Section: Torrefaction Processesmentioning
confidence: 99%
“…Their study provided monetary values ranging from €0.10 to €128.20 per milligram of active ingredient and highlighted the significant cost differences between medication types and the different water sources into which they were being emitted. Radics et al (2016) found that bioenergy production from woody biomass carried environmental costs ranging from $3.60 to $4.50 per million BTUs. Lastly, Tol's (2018) review of the economic impacts of climate change found that "a global mean temperature rise of 2.5°C would make the average person feel as if she had lost 1.3% of her income."…”
Section: Introductionmentioning
confidence: 99%